Electrical and thermal performance evaluation of solar Photovoltaic/Thermal (PV/T) air system / Nurul Ataillah Abdul Rahim - Nurul Ataillah , Abdul Rahim (2013)
Major application of monocrystalline PV modules is to convert solar energy into electrical energy. One of the weaknesses of PV module is its efficiency is depends on temperature. In simple way, it can be describe that as temperature increase, the efficiency of PV module decrease. Most of the researchers nowadays recommend using PVT concept in order to decrease the PV temperature. Solar PVT collectors are devices that convert solar energy into electrical and thermal energy. They are available in several designs, but the basic operating principles remain the same which is to collect heat generated from PV module to increase its efficiency. Combination of PV module and thermal collector with flowing fluid to extract heat will provide electrical and thermal output at low cost which is a benefit in renewable energy field. In this research, an indoor and outdoor testing to investigate the electrical and thermal performance of air based PV/T system has been carried out. A new design of thermal collector has been proposed. The structure has been attached to the PV module before running the experiment. The experiment is conducted indoors with controlled environment and several conditions. During indoor testing, parameters like angle, irradiation level and air speed are varied in order to differentiate the performance of PVT system under such conditions. As irradiation level increases, the electrical efficiency decreases. This is due to the rapid increment of temperature as irradiation level increases. The data collected is compared to PV module without thermal collector. Field experiments under Malaysia’s climate are conducted and compared with indoor testing. There is not much difference in electrical and thermal efficiency for every system since the PV module used is too small. Compared to indoor testing, low thermal efficiency has been achieved for outdoor testing. This is due to the variation of irradiation level where it is not constant like during indoor testing. From both experiment, electrical efficiency achieved is around 10% while thermal efficiency is 9%.